STUDI LITERATUR PERKEMBANGAN GREEN BUILDING DI INDONESIA - Bayu Widiarsa Kadek; INS Kumara; Rukmi Sari Hartati (Program Studi Teknik Elektro UNUD, 2021)
Green building is an alternative to anticipate damage to the earth due to development activities. This studyreviews the development of green building inkIndonesia with a systematic literature method. The reviewthat was carried out included regulations, implementation and implementation of green building inIndonesia. The development of government regulations on green buildings requires that every buildingmeet the criteria of a green building. There are 20 buildings that have been certified green building by 2018with the gold to platinum category. Research in the field of green building has also developed with 53scientific publications. From the latest reviews, it is found that the implementation of green building inIndonesia has been carried out in various aspects of the building. In the future, policies and regulations atthe national and regional levels are integrated with each other to implement green buildingcomprehensively in Indonesia.